(untitled) (Papeles, 2012)
The purpose of this research project is to publicize the appreciation that students have in one program of psychology of Bogotá, Colombia, in relation with the teaching methods to generate a meaningful learning. This research conducted a focus group with a sample to a regular students of the faculty, then the results they received a triangulation with the answer obtained in a semi-structured interviews applied to another sample of students from the same faculty, to confirm the findings of the focus group. This instrument was validated by three expert judges. The technique used to analyze the perceptions of the students was the discourse analysis. In the first question that specifically inquires about the perception of the teaching methods of planning, it was found that according to the students, if there are educational curriculum that allows you to generate meaningful learning because the themes are judiciously prepared by the teachers. In the second question, that disputed on the teaching methods for training in procedures, skills and abilities, participants indicated a constant use of various educational methods, where it promotes the understanding and learning of concepts, methodologies and skills articulated with real life. In the last question that refers to the relevance of the techniques used by teachers to give their subjects, the participants agreed that the techniques are appropriate when directly involve the student in the development of the thematic content, for other hand if the teachers are dedicated to enact their classes in a traditional way (the discourse class), do not facilitate the significance of knowledge. The students think that the evaluation of the learning is a tool that generates significant learning when it is realized immediately afterwards to explain to the students. It is necessary to say in addition, that to get the students feeling the key is the permanency of the teachers work in the same theme or areas, because they can develop the implementation of a better didactics, so in his perception the teachers who generate major significant learning are those who go long time in the same area of knowledge.